Practices of Intensive Care Unit Nurses in Maintaining Patient Body Hygiene - Aljesham, Amenah Abd Al Hassan Jebur (Journal of Science in Medicine and Life, 2025)
Background: Patient hygiene is a vital component of nursing care in Intensive Care Units (ICUs), where critically ill and immobilized patients are highly dependent on nurses for their basic needs. Effective hygiene practices prevent healthcare-associated infections (HAIs), maintain skin integrity, and enhance patient comfort. Despite its importance, hygiene care is often neglected in critical care settings due to workload, resource constraints, and the prioritization of life-saving interventions. In Iraq, limited research exists regarding ICU nurses’ hygiene practices, making this study significant for improving patient safety and care quality. Objectives: To assess the practices of ICU nurses in maintaining patient body hygiene, identify areas of strength and weakness, and determine the influence of demographic and employment characteristics on these practices. Methodology: A descriptive cross-sectional study was conducted from February 9, 2023, to June 26, 2024, at Hilla Teaching Hospital ICU. A convenience sample of 125 nurses participated. Data were collected using a structured questionnaire developed after literature review, consisting of two parts: Part I: Socio-demographic and employment data (age, gender, education, marital status, experience). Part II: Practices related to various aspects of hygiene care. The instrument’s reliability was confirmed with Cronbach’s Alpha = 0.84. Data collection occurred between March 17 and May 15, 2024, and analysis was performed using SPSS version 26. Results: The majority of nurses were aged 20–30 years (83.6%), female (69.1%), and college graduates (66.4%). Most had 1–10 years of experience (64.6%) and less than 5 years in ICU (52.7%). Overall, the nurses demonstrated a fair level of practice across all domains. Best performance: Hand hygiene before care (Mean = 2.48, good practice). Lowest performance: Use and disposal of PPE, drying the skin, and hair/nail care (Mean ≤ 1.6, poor practice). The general mean across all domains indicated fair practice (1.6–2.39). Findings revealed gaps in environmental preparation, catheter care, and infection control measures, despite moderate adherence to assessment and oral hygiene practices. Conclusion: ICU nurses demonstrated fair overall performance in maintaining patient body hygiene, with deficiencies in PPE use, environmental readiness, and detailed hygiene procedures. Although most participants held higher education levels, practical application of evidence-based hygiene care was inconsistent. Factors such as limited training, staff shortages, and lack of institutional support may contribute to these gaps.